Modelling and analysis of offshore energy hubs - Zhang, Hongyu; Tomasgard, Asgeir; Knudsen, Brage Rugstad; Svendsen, Harald G.; Bakker, Steffen J.; Grossmann, Ignacio E. (Energy (Oxford), 2022)
Clean offshore energy hubs may become pivotal for efficient offshore wind power generation and distribution. In addition, offshore energy hubs may provide decarbonised energy supply for maritime transport, oil and gas recovery, and offshore farming, while also enabling conversion and storage of liquefied decarbonised energy carriers for export. In this paper, the role of offshore energy hubs is investigated in the transition of an offshore energy system towards zero-emission energy supply. A mixed-integer linear programming model is developed for investment planning and operational optimisation to achieve decarbonisation at minimum cost. We consider offshore wind, solar, energy hubs and subsea cables. A sensitivity analysis is conducted on CO2 tax, CO2 budget and the capacity of power from shore. The results show that: (a) a hard carbon cap is necessary for stimulating a zero-emission offshore energy system, (b) offshore wind integration and power from shore can more than halve current emissions, but offshore energy hubs with storage may be necessary for zero-emission production, and (c) at certain CO2 tax levels, the system with offshore energy hubs can potentially reduce CO2 emissions by 49% and energy losses by 10%, compared to a system with only offshore renewables, gas turbines and power from shore. •A mixed-integer linear program for large-scale offshore energy system planning.•Investment planning with operational details of offshore oil and gas fields.•Sensitivity analysis on CO2 tax, carbon budget and onshore power capacity.•Offshore energy hubs show value in emission reduction, energy losses and costs.